Selected Abstracts of the 2nd International Workshop "Intensive Care of the Newborn"; Verona (Italy); March 9-10, 2018 - Erratum - - (Hygeia Press di Corridori Marinella, 2018)
This is an erratum to: Selected Abstracts of the 2nd International Workshop "Intensive Care of the Newborn"; Verona (Italy); March 9-10, 2018. J Pediatr Neonat Individual Med. 2018;7(1):e070125. doi: 10.7363/070125. Inadvertently, we introduced errors into ABS 10 during the editing process. To correct those errors, we are now publishing a corrected version of the entire abstract: ABS 10. NEONATAL/INFANTILE PYKNOCYTOSIS. AN UNUSUAL CASE OF HAEMOLYTIC ANEMIA • R. Sokou, G. Patsouras, K. Lampropoulou, E. Tavoulari, K. Adamopoulos, M. Theodoraki, M. Kollia, A. Konstantinidi